The Effect of ESG Disclosure on Firm Value With Independent Commissioners as A Moderating Variable - Regina Diah Retno Ayu; Tarsisius Renald Suganda; Lalu Rahmat Sohdi; Rino Tam Cahyadi (Economics and Business Journal (ECBIS), 2026)
The increasing demand for corporate transparency in sustainability practices, the development of ESG reporting regulations in Indonesia, and the persistent issues of credibility in disclosures such as greenwashing and inconsistent information quality indicate that Environmental, Social, and Governance (ESG) disclosures are not always perceived positively by the market. This condition is important because ESG disclosures that are not supported by substantive implementation may be viewed as an additional cost, risk, or merely a form of compliance, which in turn may reduce firm value. Therefore, this study aims to analyze the effect of environmental disclosure, social disclosure, and governance disclosure on firm value by incorporating independent commissioners as a moderating variable. Firm value is measured using Tobin’s Q because it reflects market valuation of the company’s performance and growth prospects. The sample consists of companies included in the SRI-KEHATI index during the 2020–2024 period, with a total of 227 unbalanced panel observations analyzed using panel data regression. The results show that environmental disclosure, social disclosure, and governance disclosure have a negative and significant effect on firm value. Independent commissioners are able to weaken the negative effect of environmental disclosure and governance disclosure on firm value, but they are unable to moderate the relationship between social disclosure and firm value. These findings suggest that ESG disclosure in sustainability-oriented companies is not yet fully perceived as a value-creating factor when it is not supported by convincing implementation quality. Practically, these findings are intended to encourage companies not only to increase the extent of ESG disclosure, but also to strengthen the substantive implementation and supervisory role of independent commissioners to enhance the credibility of sustainability information